Surgically Discovered Xanthogranulomatous Pyelonephritis Invading Inferior Vena Cava with Coexisting Renal Cell Carcinoma - Henry M. Rosevear; Melissa M. Meier; Brian L. Gallagher; Fadi N. Joudi (The Scientific World Journal)
Xanthogranulomatous pyelonephritis (XGP) is a chronic inflammatory process that results in replacement of renal and/or perirenal tissue with a diffuse infiltrate of inflammatory cells referred to as xanthoma cells. We present a case of a 49-year-old man with an incidentally discovered renal mass with inferior vena cava (IVC) thrombus, who was found intraoperatively to have a significant inflammatory process involving the posterior wall of his IVC and right renal vein consistent with XGP surrounding a focus of clear cell renal cell carcinoma in the midportion of his right kidney.